Efektivitas Peran Kepolisian dalam Operasi Anti Narkotika sebagai Bentuk Pemberantasan Kejahatan Narkotika di Kabupaten Sidenreng Rappang - Hardiyanti, Tiya; Pawennai, Mulyati; Ahmad, Kamri (Innovative: Journal Of Social Science Research, 2025)
The police have a special operation known as the anti-narcotics operation, which aims to eradicate drug trafficking crimes, particularly those carried out by the Sidenreng Rappang Police. This study will examine the effectiveness of the Sidenreng Rappang Police in carrying out anti-narcotics operations in the Sidrap jurisdiction and the factors that influence the effectiveness of the Sidenreng Rappang Police in carrying out anti-narcotics operations. This research is a legal study with an empirical approach and a qualitative descriptive method. The research location is in Sidenreng Rappang District. The types and sources of data for this study consist of the police as the primary source, and documents, archives, or literature related to the topic as secondary sources. The population and sample were taken from a number of cases caught in the anti-narcotics operations of the Sidenreng Rappang Police Department from 2022 to 2024. Data collection techniques used interviews and literature review. This study employed qualitative data analysis techniques by interpreting the data using sentences. The results of this study indicate that the anti-narcotics operations conducted by the Sidenreng Rappang Police Department from 2022 to 2024 have been effective. There has been an increase in enforcement against drug traffickers, the implementation of criminal sanctions, and rehabilitation for drug offenders. The recommendation in this study is to increase operations each year as evidence of the police's seriousness in eradicating drug trafficking and optimizing criminal sanctions against perpetrators, as well as encouraging the involvement of local governments and communities in supporting the anti-drug movement. Keywords: Effectiveness, anti-narcotics operations, crime